1999
DOI: 10.1073/pnas.96.24.13904
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes controlled by quorum sensing in Pseudomonas aeruginosa

Abstract: Bacteria communicate with each other to coordinate expression of specific genes in a cell density-dependent fashion, a phenomenon called quorum sensing and response. Although we know that quorum sensing via acyl-homoserine lactone (HSL) signals controls expression of several virulence genes in the human pathogen Pseudomonas aeruginosa, the number and types of genes controlled by quorum sensing have not been studied systematically. We have constructed a library of random insertions in the chromosome of a P. aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
594
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 608 publications
(630 citation statements)
references
References 46 publications
26
594
1
3
Order By: Relevance
“…The LuxR\ LuxI type of quorum-sensing regulation has been shown to control the expression of an increasing number of genes, including peptide synthetase genes, exopolysaccharide genes and virulence factors, especially in host-associated bacteria such as Pseudomonas aeruginosa, Erwinia carotovora and Agrobacterium tumefaciens (Rhizobium tumefaciens) (Whiteley et al, 1999 ;Bassler, 1999). In Gram-negative bacteria quorumsensing systems consist of an N-acylhomoserine lactone (AHL) signal molecule (autoinducer), which is synthesized by a LuxI homologue, and requires an autoinducer-dependent transcriptional activator protein, as represented by LuxR (Whiteley et al, 1999). At least two different types of AHLs were shown to regulate the rhiABC operon in a cell-density-dependent manner (Rodelas et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The LuxR\ LuxI type of quorum-sensing regulation has been shown to control the expression of an increasing number of genes, including peptide synthetase genes, exopolysaccharide genes and virulence factors, especially in host-associated bacteria such as Pseudomonas aeruginosa, Erwinia carotovora and Agrobacterium tumefaciens (Rhizobium tumefaciens) (Whiteley et al, 1999 ;Bassler, 1999). In Gram-negative bacteria quorumsensing systems consist of an N-acylhomoserine lactone (AHL) signal molecule (autoinducer), which is synthesized by a LuxI homologue, and requires an autoinducer-dependent transcriptional activator protein, as represented by LuxR (Whiteley et al, 1999). At least two different types of AHLs were shown to regulate the rhiABC operon in a cell-density-dependent manner (Rodelas et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Up to 11 % of the P. aeruginosa genome is subjected to QS-dependent regulation [18]. Inhibition of QS offers a new hope for combating multi-antibiotic-resistant bacteria, because it does not impose harsh selective pressure for the development of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The Pseudomonas aeruginosa is highly tolerant to antibiotic treatment largely due to the biofilm [16]. Since QS system was found to be essential for creation of mature, (1) 1.51 %, (2) 1.817 %, and (3) 96.673 % differentiated biofilms [17], we also tested if the final extract of strain 4001 exhibited a similar inhibition effect on biofilm formation.…”
Section: Final Extract Has Some Effect On Biofilm Formationmentioning
confidence: 99%
“…Next, we tested whether quorum sensing, which controls virulence, antimicrobial activity, and biofilm formation for P. aeruginosa (Whiteley et al, 1999;Wagner et al, 2003), was upregulated with 2,3-butanediol compared with glucose. Quorum sensing in P. aeruginosa is mediated by diffusible acylhomoserine lactones that are produced by LasI, which synthesizes 3-oxo-dodecadonyl homoserine lactone (3O-C12-HSL), and RhlI, which synthesizes n-butyryl homoserine lactone (C4-HSL).…”
Section: Resultsmentioning
confidence: 99%
“…Research had already indicated that reduced PCA and PYO were considerably more reactive with Fe(III) and O 2 , respectively, than vice versa (Wang and Newman, 2008). Importantly, the quorum-sensing cascade regulates phenazine production by P. aeruginosa (Whiteley et al, 1999), and thus has an effect on the redox activity of the produced phenazines (Venkataraman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%